The Gospel to the Romans: The Setting and Rhetoric of Mark's Gospel. By Brian J. Incigneri - Telford, William R. (The journal of theological studies, 2007)
The subtitle of Brian Incigneri's book The Gospel to the Romans states that it is about the setting and rhetoric of Mark's Gospel, hence indicating that it has both a historical and a literary focus. The combination is to be noted. An exercise in historical criticism combined with rhetorical analysis, this scholarly book will attract academics, postgraduate students, and informed laypersons with an interest in biblical studies, literary criticism, and/or classical history. Discussion on the date and location of the first Gospel, of course, has a long, distinguished and, to date, inconclusive history, and Incigneri's advocacy of a Roman provenance and a date during the reign of Vespasian (soon after July/August 71 ce, to be precise) is not unparalleled. M.